Cryptocurrencies: Business Students’ Awareness and Universities’ Adoption Readiness and Compatibility of Use Considering the Mediation of Attitudes - Eric S Parilla; Marc Edward Abadilla (Applied Quantitative Analysis, 2022)
The study aims to determine the effect of awareness of business students towards cryptocurrencies and readiness of universities and colleges to accept cryptocurrencies as a medium of exchange considering the mediation of business students’ attitude. The research used partial least squares structural equation modeling (PLS-SEM) and deployed a questionnaire attuned to the awareness and attitudes of business students towards cryptocurrencies and readiness and compatibility of use to universities and colleges in Ilocos Norte. The output of the investigation revealed that awareness of business students are not correlated to readiness of universities and colleges which means that even though students understand cryptocurrencies, it is not an assurance that universities and colleges are ready to accept it as medium of exchange. The study proposes that trainings and seminars for business students and professionals should be conducted to expand understanding and acceptance of cryptocurrencies.